The Breath of awareness - charuwat (Ratana Thanthammo) , Phrakhru Sobhon (Journal of Buddhist Innovation Review, 2025)
This article presents a method to extinguish suffering with the breath of awareness according to the Ānāpānasati method. The wind element is one of the four great elements. All elements are said to be the same. With its ability to be a form, a great element, a dhamma, and something impermanent, constantly oppressed, suffering in nature, and unable to be controlled. The Lord Buddha discovered the method to extinguish suffering by practicing the 16 steps of Ānāpānasati meditation, which is a process of training mindfulness to be in the present moment, such as determining the breath in and out. When the breath touches the tip of the nose, you know it. When you breathe in, you know it. When you breathe out, you know it. Attach mindfulness to the breath in and out only. This is called Ānāpānasati, which is mindfulness determining the breath in and out. When you do mindfulness like this continuously, concentration will arise, which is the mind and emotion are firmly attached to the breath. Those who practice Ānāpānasati are not only practicing Samatha meditation, but are also practicing Vipassanā meditation continuously. Ānāpānasati is a meditation that is complete in itself. The value and benefits of Ānāpānasati in daily life in 4 aspects are: (1) Physical development helps to make the body strong and healthy. (2) Mental development helps to make a person with complete mental health. Having a happy mind (3) in terms of social development, those who develop their bodies and minds are ready to be a force supporting society to develop further, and (4) in terms of intellectual development, it is the knowledge and understanding of the truth of all things according to causes and conditions, being enlightened, free from defilements, extinguishing suffering with the breath of awareness.